Research on the Supervision Mechanism of Voluntary Food Safety Information Disclosure: An Evolutionary Game Analysis - Wentai Bi; Suyun Chen; Panpan Zhu; Zongze Li; Qingzi Cao (SAGE Open)
Food safety is a significant livelihood and critical social security issue. However, few people are aware of the interests of multiple actors in the voluntary disclosure of food safety information. In order to solve the “market failure” and “government failure” caused by information asymmetry in the Chinese food market, this study constructs a game model of voluntary food safety information disclosure consisting of food enterprises, consumers, and the government. Stable equilibrium points and optimal decision-making strategies under different constraints were analyzed using replicated dynamic equations. Matlab software was used to simulate the game model to examine the interaction of the three parties in strategy selection, and an econometric model was used for empirical testing to clarify the interaction between the interests and behaviors of each party. The study results show that the interests of food enterprises, consumers, and the government and the realization of their claims have become critical constraints on food safety. Food enterprises are responsible for the voluntary disclosure of food safety information. Consumers and governments should strengthen collaborative supervision and linkage mechanisms to actively guide them toward substantive information disclosure. Government penalties, consumer subsidies, and food enterprises rewards for substantive information disclosure strategies can effectively promote substantive information disclosure by food enterprises. Therefore, this study contributes to a comprehensive understanding of the micro-mechanisms and differential impact effects of voluntary food safety information disclosure and provides a reference for decision-making to improve the quality of voluntary corporate food safety information disclosure and promote the modernization of the food safety governance system and governance capacity.